Effect of Work Environment, Work Conflict, and Work Stress on Employee Performance at Mercure Hotel Bengkulu - Ratna Putriyanti; Yulius Wahyu Setiadi (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of the work environment, work conflict and work stress on employee performance at the Mercure Hotel Bengkulu. This type of research is a survey research with a quantitative approach, the object of this research is the employees at the Mercure Hotel Bengkulu which is precisely located on Jl. S. Parman No.27, Padang Jati, Kec. Ratu Samban, Bengkulu City with the sampling method, namely the total sampling technique. The number of respondents in this study was 50 people. In this research, the authors use data collection methods by means of observation, interviews and distributing questionnaires. By using data analysis techniques using test instruments namely validity test and reliability test, classical assumption test, namely multicollinearity test, normality test. and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Coefficient of Determination (R2), and Hypothesis Test, namely t test and f test. The results of this study can be concluded that the Work Environment variable has a partially significant effect on the Employee Performance of Mercure Hotel Bengkulu, Work Conflict has a partially significant effect on the Employee Performance of Mercure Hotel Bengkulu, Job stress has a partially significant effect on the Employee Performance of Mercure Hotel Bengkulu, and the Work Environment. Work Conflict and Job Stress have a significant effect simultaneously on Employee Performance at Mercure Hotel Bengkulu.